Leadership and Communication: the Customization of Politics - Laguna Platero, Antonio (Anàlisi, 2011)
Are politics possible with no leaders? Who wins an election, the leader or the party? Is the leader born, or he becomes so through mass media? As you see, we are facing vital issues for nowadays politics. The leader’s role has protagonised politics since long ago, but in ours times it has taken a new dimension because of several factors. Firstly, now that television, the main source of political information for society, has imposed personalization as the general means of communication. The television image is focused on people, not in the ideas or programs. Leaders who aim at electoral victory, must overcame the test of notoriety. Only through mass media, citizens can evaluate what should their vote be. In this way, more and more people ascribe the responsibility of becoming the main point of reference for democratic decisions to the face that gives name to all the political strategy behind it.